Analisis Pendapatan Pedagang Kambing di Pasar Hewan Terpadu Wlingi Kabupaten Blitar - Syaniatul Hanim (Journal of Livestock Science and Production, 2025)
The purpose of this study was to determine the income of goat traders in the Integrated Animal Market Wlingi Blitar Regency. The material used in this research process is goat traders in the integrated animal market of Wlingi Blitar Regency, the approach used is a quantitative approach with a survey method in the form of a case study. Data collection techniques using interviews and documentation with a list of structured open questions prepared based on the instrument. The main parameter measured was the income of traders which was analyzed by the formula Pd=TR-TC (Profit = Total Revenue - Total Cost). The results showed that the income of goat traders varieddepending on the scale of livestock sales. In addition to income, this study also analyzed the ReturnCost Ratio (R/C) to assess profitability at different sales scales. The highest profit was obtained at the sales scale of 31-40 heads, followed by the sales scale of 41-50 heads, then thesales scale of 10-20 heads, then the sales scale of 21-30 ecoe, the lowest profit was at the sales scale above 51 heads. The average R/C ratio at all scales was 1.1, indicating that the goat trading business in this market is generally profitable, with each unit of cost generating a positive profit. Analysis of the R/C value confirms that this business is still a viable and profitable business, especially at certain sales scales